Gender-affirming hormone therapy in cystic fibrosis – A case of new Pseudomonas infection. (2021) - Shaffer, L.; Bozkanat, K.; Lau, M.; Sharma, P.; Sathe, M.; Lopez, X.; Jain, R.
Abstract: Background: Little is known about the impact of hormone therapy on transgender youth with Cystic Fibrosis (CF). This case report describes an 18-year-old affirmed female with CF who was treated with hormone therapy associated in timing with new growth of Pseudomonas aeruginosa in her sputum culture. Discussion: We highlight important considerations, including the impact of gender-affirming hormone therapy on overall CF disease course. Evidence supports that females with CF have worse outcomes than males, which are partly attributed to estrogen effects. Pseudomonas aeruginosa is one of the most prevalent pathogens in people with CF. Here, we highlight a transfemale who grows Pseudomonas aeruginosa for the first time since her youth, nearly 1 year after starting estrogen therapy. This is consistent with previous literature of an association between high estrogen levels and Pseudomonas aeruginosa prevalence, but has never been evaluated in a transgender population. Conclusion: Through this case, we demonstrate the need for additional research to understand the relationship between gender-affirmative hormone transition and CF care and management.